Distribution Prediction and Adaptability Analysis of Section Camellia Plants (Camellia Genus) in China Based on the MaxEnt Model - Weihao Gu; Xu Xiao; Zhaohui Ran; Chao Yan; Dongzhen Jiang; Lei Zhou; Mingtai An; Zhi Li (Ecology and Evolution, 2025)
ABSTRACT Sect. Camellia plants, widely distributed across southern China, hold significant economic value through their dual applications in landscape greening, ornamental horticulture, and oilseed production. However, with rapid changes in the global climate, it is becoming increasingly important to study the habitat distributions of species and the factors influencing their adaptations. Using the maximum entropy model, we predicted the past, present, and future distribution areas of suitable habitats for sect. Camellia under different climate scenarios. The results revealed that under current climate conditions, the total suitable area of sect. Camellia was 17.04 × 105 km2, and the highly suitable area was 1.95 × 105 km2. The distribution of sect. Camellia was strongly influenced by key environmental factors, such as the maximum temperature in the hottest month (Bio5), the minimum temperature in the coldest month (Bio6), the annual difference in temperature (Bio7), and the slope (Slope). In view of future climate change, the suitable distribution center of sect. Camellia is expected to shift to higher latitudes and may undergo northward movement to adapt to new environmental conditions, leading to an expansion of the total suitable area.